Pengembangan Lkpd Menulis Teks Eksplanasi Berbasis Model Pembelajaran Kooperatif Tipe Stad - Klara Ken Laras; Mulyanto Widodo; Edi Suyanto (Universitas Lampung, 2018)
The purpose of this research is to produce the product of teaching materials and to describe the feasibility of teaching materials in the form of LKPD of Writing Explanation Text based on Cooperative Learning Model with STAD type. The method of this research according to the research and development method by adapting seven out of ten steps according to Borg and Gall. The result of the research (1) has been developed a teaching materials LKPD of Writing Explanation Text based on Coopartive Learning Model with the STAD type, (2) the assessment result of the teaching materials as a whole is stated